THE EFFECT OF PROFITABILITY, LEVERAGE AND COMPANY SIZE ON TAX AVOIDANCE (EMPIRICAL STUDY ON BASIC AND CHEMICAL INDUSTRY COMPANIES LISTED ON THE IDX) - Febryani Putri; Masta Sembiring (SEAN Institute, 2022)
This study was conducted to determine “The Effect of Profitability, Leverage and Company Size on Tax Avoidance (Empirical Study on Basic and Chemical Industrial Companies Listed on the IDX). The type of research used is quantitative research. The population in this study are 19 basic and chemical industrial companies. Listed on the Indonesia stock Exchange in 2016 – 2020. The method used in this study to determine the sample is purposive sampling with as many as 9 companies for 5 consecutive years. The data collection used is the documentation method by taking financial statement data on the Indonesia Stock Exchange. Ready to be processed then will be tested using SPSS version 21.0. the data analysis methods used in this research are descriptive statistics, multiple linear regression, classical assumption test, and hypothesis. Based on the result of the study, it was found that, (1) Profitability did not have asifnificant effect on the tax avoidance; (2) Leverage has an effect on the tax avoidance: (3) Company size has no effect on tax avoidance. Based on the F test that profitability, leverage and company size have a simultaneous effect on tax avoidance